2019
DOI: 10.1016/j.fertnstert.2019.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Changes in diet composition with urbanization and its effect on the polycystic ovarian syndrome phenotype in a Western Indian population

Abstract: Objective: To study the effects of increasingly prosperous diet content on clinical features of polycystic ovary syndrome (PCOS). Design: A cross-sectional cohort study of 711 women with PCOS from a heterogeneous population spanning a wide spectrum of socioeconomic strata. Setting: Independent hospital. Patient(s): A total of 711 women with PCOS in whom the diagnosis was based on Rotterdam criteria. Results were compared with a locally recruited reference group. Intervention(s): Clinical assessment of women wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…We used an FSH concentration of >25 IU/L as a diagnostic criterion for PCOS with DOR according to the guideline development group recommendation. 6 Kulkarni et al 7 observed associations of an increasingly affluent diet and high BMI with the incidence of PCOS. Weight management is a first-line treatment for women with PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…We used an FSH concentration of >25 IU/L as a diagnostic criterion for PCOS with DOR according to the guideline development group recommendation. 6 Kulkarni et al 7 observed associations of an increasingly affluent diet and high BMI with the incidence of PCOS. Weight management is a first-line treatment for women with PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical trial, women with PCOS who were placed on a vegan diet (39% African-Americans) lost significantly more weight than participants on a regular diet [101]. A cohort study in 711 Indian women found that the shift from a vegetarian dietary pattern to a meat-based pattern with urbanization increased a woman's risk for PCOS [102]. However, more research is needed on the effects of plant-based diets on PCOS.…”
Section: Obesitymentioning
confidence: 99%
“…The findings from the study by Kulkarni et al (2) demonstrate the paradoxical relationships between India's urbanization, socioeconomic classes, and health management as compared with other Westernized nations. Inconsistencies in the setting where PCOS occurs makes finding a universal resolution more difficult.…”
mentioning
confidence: 97%
“…Kulkarni et al (2) found statistically significantly increased measures of antim€ ullerian hormone, obesity, and hirsutism in urban Indian women with PCOS who consumed a WSD. Overall, the PCOS phenotype was worse in urban areas; a 89% prevalence of hirsutism was found in urban women who consumed a WSD compared with 22% among rural women who ate a vegetarian diet.…”
mentioning
confidence: 99%
See 1 more Smart Citation